Risk of secondary malignant neoplasms in children following proton therapy vs. photon therapy for primary CNS tumors: A systematic review and meta-analysis - Upadhyay, Rituraj; Yadav, Divya; Venkatesulu, Bhanu P.; Singh, Raj; Baliga, Sujith; Raval, Raju R.; Lazow, Margot A.; Salloum, Ralph; Fouladi, Maryam; Mardis, Elaine R.; Zaorsky, Nicholas G.; Trifiletti, Daniel M.; et al. (Frontiers in Oncology, 2022)
Background: Central nervous system tumors are now the most common primary neoplasms seen in children and radiation therapy is a key component in management. Secondary malignant neoplasms (SMNs) are rare, but dreaded complications. Proton beam therapy (PBT) can potentially minimize the risk of SMNs compared to conventional photon radiation therapy (RT) and multiple recent studies with mature data have reported the risk of SMNs after PBT. We performed this systematic review and meta-analysis to characterize and compare the incidence of SMNs after proton and photon-based radiation for pediatric CNS tumors. Methods: A systematic search of literature on electronic (PubMed, Cochrane Central, and Embase) databases was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. We included studies reporting incidence and nature of SMNs in pediatric patients with primary CNS tumors. The crude incidence of SMNs and all secondary neoplasms were separately extracted, and the random-effects model was used for pooled analysis and subgroup comparison was performed between studies using photons vs protons. Results: Twenty-four studies were included for analysis. A total of 418 SMNs were seen in 38163 patients. The most common SMN were gliomas (40.6%) followed by meningiomas (38.7%), sarcomas (4.8%), and thyroid cancers (4.2%). The median follow-up was 8.8 years [3.3-23.2].The median latency to SMN for photons and protons were 11.9 years [5-23] and 5.9 years [5-6.7], respectively. The pooled incidence of SMNs was 1.8% (95% CI: 1.1% – 2.6%, I2=94%) with photons and 1.5% (95% CI: 0 - 4.5%, I2=81%) with protons. The pooled incidence of all SNs was not different [photons: 3.6% (95% CI: 2.5% – 4.8%, I2=96%) vs protons: 1.5% (95% CI: 0 – 4.5%, I2=80%); p = 0.21]. Conclusion: We observed similar rates of SMN with PBT at 1.5% compared to 1.8% with photon-based RT for pediatric CNS tumors. We observed a shorter latency to SMN with PBT compared to RT. With increasing use of pencil beam scanning PBT and VMAT, further studies are warranted to evaluate the risk of secondary cancers in patients treated with these newer modalities.